2021
DOI: 10.1007/s13225-021-00477-7
|View full text |Cite
|
Sign up to set email alerts
|

Species in lichen-forming fungi: balancing between conceptual and practical considerations, and between phenotype and phylogenomics

Abstract: Lichens are symbiotic associations resulting from interactions among fungi (primary and secondary mycobionts), algae and/or cyanobacteria (primary and secondary photobionts), and specific elements of the bacterial microbiome associated with the lichen thallus. The question of what is a species, both concerning the lichen as a whole and its main fungal component, the primary mycobiont, has faced many challenges throughout history and has reached new dimensions with the advent of molecular phylogenetics and phyl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 488 publications
1
47
0
1
Order By: Relevance
“…In the hitherto studied species, based on the aforementioned and the present study, the factor of hidden diversity in presumably known species ranges from twofold (e.g., Racoplaca maculata, R. melanobapha; Strigula microspora, S. nitidula) to threefold (e.g., Puiggariella nemathora, R. subtilissima, Strigula concreta) to up to fivefold (S. antillarum, S. smaragdula), for a weighted mean of a threefold increase. These findings align well with Lücking et al [36], who also showed multiplication factors between two and five in studied species complexes. Given that the data on Strigulaceae are mostly from Southeast Asia, even higher multiplication factors (a weighted mean of up to five) could be assumed when expanding such studies to tropical America and Africa.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the hitherto studied species, based on the aforementioned and the present study, the factor of hidden diversity in presumably known species ranges from twofold (e.g., Racoplaca maculata, R. melanobapha; Strigula microspora, S. nitidula) to threefold (e.g., Puiggariella nemathora, R. subtilissima, Strigula concreta) to up to fivefold (S. antillarum, S. smaragdula), for a weighted mean of a threefold increase. These findings align well with Lücking et al [36], who also showed multiplication factors between two and five in studied species complexes. Given that the data on Strigulaceae are mostly from Southeast Asia, even higher multiplication factors (a weighted mean of up to five) could be assumed when expanding such studies to tropical America and Africa.…”
Section: Discussionsupporting
confidence: 93%
“…Given that R. maculatoides has distinctly shorter (15-25 µm vs. 22.5-27.5 µm long) ascospores and macroconidia with shorter appendages (10-18 µm vs. 17-35 µm), we consider R. macrospora a recently emerging, yet distinct species. Species evolving from paraphyletic residuals are now broadly accepted [36], but an artifactually paraphyletic topology could also result from the most closely related species not having been sequenced yet. Another possible explanation is that R. maculatoides itself represents a species complex.…”
Section: Species Tree Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Such careful and versatile analysis of distinct phylogenetic lineages may lead to recognising some previously-overlooked characteristics ( Kroken and Taylor 2001 ; del Prado et al 2007 ; Frolov et al 2016 ; Leavitt et al 2016 ; Szczepańska et al 2020 ). In the recent review paper, Lücking et al (2021) proposed a detailed protocol for consistent taxonomy of lichen-forming fungi. The integrative taxonomy employing phylogeny, reproductive biology and phenotype should be used to delimit species ( Lücking et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also noted that description of a new species, based on single-locus phylogenetic analyses, could only be done in exceptional cases. The errors caused by contaminant sequences, laboratory mix-ups and chimeric sequences should be avoided for proper establishment of novel taxa, based on molecular data only ( Lücking et al 2021 ). Therefore, it is crucial to employ unlinked loci from different parts of the genome, even though the ITS rDNA marker is widely used in DNA barcoding of fungal taxa.…”
Section: Discussionmentioning
confidence: 99%